The effects of nutrition counseling on dietary compliance and blood sugar levels of type 2 diabetes mellitus patients - Silvia Wagustina; Nunung Sri Mulyani; Nailatul Amani (Jurusan Gizi, Poltekkes Kemenkes Aceh, 2021)
One of the efforts to increase individuals’ or families’ knowledge and ability of nutrition is nutrition counseling. Patients are entitled to qualified nutrition counseling because it is an integral part to accelerate their healing process. Type II DM patients’ compliance with diet therapy is a difficult problem to control. Some studies showed that 75% of patients did not comply with the recommended diet, and 53% had poor blood glucose control. This study employed an experimental study with a quasi-experimental design as well as a pretest and posttest without a control. The sample of this study was 30 people. This study was conducted in Meuraxa Regional General Hospital, Banda Aceh from June to July 2017. The primary and secondary data were analyzed using the statistical test of T-test dependent and chi-square test with a level of confidence (0:05). Th Moreover, before the counseling, the average of their blood sugar levels was 318.13, but after the counseling, their blood sugar levels decreased by 273.20 mg/dl; thus, the margin of decline was 42.167 mg/dl. The chi-square test discovered that the nutrition counseling significantly influenced adherence and obtained a p-value of <0.05. Meanwhile, the dependent t-test showed that the blood sugar levels of the type II diabetes patients were p<0.05. It is expected that the nutrition officers provide continuous or sustainable nutrition counseling to increase the patients’ knowledge and dietary compliance and help them achieve normal blood sugar levels.